Recent trends in and the outlook for health-related benefits - Sam Ray-Chaudhuri; Tom Waters (Institute for Fiscal Studies (IFS), 2024)
Individuals in the UK with health conditions may be entitled to two types of benefits - incapacity benefits (for those whose condition prevents them from working) and disability benefits (to help with extra living costs arising from the disability). Since the onset of the pandemic, there has been a substantial increase in the number of individuals claiming these 'health-related' benefits - and official projections suggest that claimant numbers will rise further still. Whoever wins the next election will have to come to terms with these trends and potentially provide a policy response. Indeed, the government has already announced a number of reforms to the health-related benefit system in the last year, including a consultation - announced by the Prime Minister in April 2024 - on tightening the disability benefit system. This report sets out the latest data on health-related benefits in the UK and discusses the evidence on potential causes for the rise, before considering the policy options.
Keywords: 330; Government finances and spending; Taxes and benefits; Benefits; Disability; Health; Government spending; Universal credit; Working age benefits